Mercury Pollution from Ilegal Gold Mining Activities and Its Impact on Human Health in the Anahoni River, Kaiely Bay, Maluku: A Review - Latuconsina, Fachrul; Syah, Nurhasan; Barlian, Eri; Umar, Iswandi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Illegal gold mining in the Anahoni River area, Kaiely Bay, Maluku, intensifies mercury pollution, posing grave environmental and health risks. Statistical analyses reveal a significant correlation between illegal mining and escalating mercury levels, necessitating urgent intervention. Environmental impacts include biomagnification in fish, affecting indigenous communities dependent on these resources. Health risks encompass neurological, reproductive, and respiratory implications, warranting targeted public health interventions. Examining the broader context, the global dimension of mercury pollution underscores the interconnected nature of the issue, requiring collaborative efforts. The toxicological aspects of mercury and its biogeochemical cycling inform potential mitigation strategies. Methodologically, systematic literature reviews, field investigations, and socio-economic assessments provide a holistic understanding of mercury contamination. Results highlight alarming mercury concentrations, with significant correlations between mercury levels, deforestation, and fish abundance, emphasizing the need for evidence-based policy decisions. Human health implications are evident through a positive correlation between mercury concentrations in river water and human hair samples, emphasizing the direct link between environmental exposure and health risks. Environmental impacts extend beyond human health, affecting ecosystems and necessitating global collaboration. The study underscores the importance of comprehensive policy frameworks, international collaborations, and community engagement in addressing the socio-economic roots of illegal gold mining. Mitigation strategies encompass regulations, sustainable practices, alternative technologies, and community-based initiatives. This review contributes to a nuanced understanding of mercury pollution in the Anahoni River, providing insights into the interconnected challenges and opportunities for sustainable solutions within a concise framework.